Home Literacy Practices And Parental Involvement in Supporting Early Childhood Language Development: A Qualitative Study - Restiana Ertika Latifah; Jamilah Mohd Basir (Murhum : Jurnal Pendidikan Anak Usia Dini, 2026)
This qualitative study explores the role of home literacy practices, prior knowledge, and supportive learning environments in shaping preschool children’s language development. Data were collected from parent and teacher interviews, along with classroom observations in Indonesian early childhood centers. Thematic analysis revealed seven dimensions of home literacy (e.g., availability of books, parental awareness, reading practices), four sub-themes of prior knowledge moderation (e.g., vocabulary familiarity, recall of book content, contextual connections, linguistic readiness), and six sub-themes of learning environment support (e.g., integration with other activities, peer interaction, motivational scaffolding). Findings demonstrate the interconnectedness of home and school literacy practices, the moderating role of prior knowledge, and the importance of emotionally supportive classroom environments. Triangulation across parents, teachers, and observations enhanced validity. This study’s novelty lies in presenting an integrated early literacy ecosystem model grounded in the Indonesian preschool context, offering a culturally situated contribution to the global discourse on emergent literacy. The study underscores the need for holistic literacy interventions that engage parents, leverage children’s prior knowledge, and create supportive school contexts.